2010
DOI: 10.1007/s11440-010-0117-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling strategy for jointed rock masses reinforced by rock bolts in tunneling practice

Abstract: This paper deals with the modeling of jointed rock masses reinforced by rock bolts. It is well known that rock bolts are extremely effective in reinforcing jointed rocks. However, if a continuum approach is adopted for modeling jointed rock masses, it is often misleading to evaluate the effectiveness of the rock bolts by numerical analyses such as the finite element method. This may be due to the fact that since no more joints exist in the continuum, the effectiveness of the rock bolts in constraining the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Bolts are widely used in major projects such as steep slopes and tunnels as an important means of reinforcing the fractured rock masses [15][16][17][18]. Many scholars have conducted extensive research on the anchoring mechanism of bolts in rock masses and achieved many meaningful results [19][20][21][22][23][24][25][26][27]. Ge and Liu [28] studied the effects of different bolt angles, material properties, and friction angles on the shear strength of the joint and proposed a formula for estimating the shear strength of the bolted joint and the optimal anchor installation angle.…”
Section: Introductionmentioning
confidence: 99%
“…Bolts are widely used in major projects such as steep slopes and tunnels as an important means of reinforcing the fractured rock masses [15][16][17][18]. Many scholars have conducted extensive research on the anchoring mechanism of bolts in rock masses and achieved many meaningful results [19][20][21][22][23][24][25][26][27]. Ge and Liu [28] studied the effects of different bolt angles, material properties, and friction angles on the shear strength of the joint and proposed a formula for estimating the shear strength of the bolted joint and the optimal anchor installation angle.…”
Section: Introductionmentioning
confidence: 99%
“…To apply correlations suggested in the present study, the modulus value of reinforced rock is required. Sakurai (1983Sakurai ( , 2010 has suggested that the modulus of reinforced rock mass can be obtained through back analysis of observed deformation. To carry out back analysis, the tunnel is analysed assuming elastic behaviour.…”
Section: Examplementioning
confidence: 99%
“…Several studies have been conducted in the past to find out the parameters, which influence the strength of the reinforced rocks. Studies conducted by Dight (1982), Egger and Zabuski (1991), Pellet and Egger (1996), McHugh and Signer (1999), and Sakurai (2010) have indicated that the strength of reinforced jointed rock depends upon the strength of parent intact rock. Further, the orientation of the joints with respect to the bolt direction has also been found to influence the strength of reinforced rock (Bjurstrom, 1974;Haas, 1976Haas, , 1981Ludvig, 1983;Pellet and Egger, 1996;Grasselli et al, 1999;and Grasselli, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Rock engineering design https://papers.acg.uwa.edu.au/p/1201_06_moyo/ still relies on experimentation as more complex theories require more testing. According to Sakurai (2008), it is difficult to demonstrate the effectiveness of rockbolts using numerical analysis; hence, the necessity of conducting physical model tests still remains.…”
Section: Introductionmentioning
confidence: 99%